2019
DOI: 10.1001/jamanetworkopen.2019.13900
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diagnostic Outcomes of RNA Genetic Testing for Hereditary Cancer

Abstract: IMPORTANCE Performing DNA genetic testing (DGT) for hereditary cancer genes is now a wellaccepted clinical practice; however, the interpretation of DNA variation remains a challenge for laboratories and clinicians. Adding RNA genetic testing (RGT) enhances DGT by clarifying the clinical actionability of hereditary cancer gene variants, thus improving clinicians' ability to accurately apply strategies for cancer risk reduction and treatment. OBJECTIVE To evaluate whether RGT is associated with improvement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 39 publications
2
54
0
1
Order By: Relevance
“…Methods that enable quantification of the proportion of aberrantly spliced transcripts arising from a variant allele, such as recently developed RNA massively parallel sequencing assays (Farber-Katz et al, 2018;Karam et al, 2019), will aid in the interpretation of cases that demonstrate expression of naturally occurring alternatively spliced transcripts and greatly improve the contribution of splicing assays to classification of sequence variants once methods for quantifying transcript expression are routinely instituted. These assays will further increase the use and utility of splicing assay data in variant classification by fulfilling the requirement of quantifying the splicing defect to ensure no full-length transcript is expressed, as currently documented in the InSiGHT MMR gene classification rules (Thompson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Methods that enable quantification of the proportion of aberrantly spliced transcripts arising from a variant allele, such as recently developed RNA massively parallel sequencing assays (Farber-Katz et al, 2018;Karam et al, 2019), will aid in the interpretation of cases that demonstrate expression of naturally occurring alternatively spliced transcripts and greatly improve the contribution of splicing assays to classification of sequence variants once methods for quantifying transcript expression are routinely instituted. These assays will further increase the use and utility of splicing assay data in variant classification by fulfilling the requirement of quantifying the splicing defect to ensure no full-length transcript is expressed, as currently documented in the InSiGHT MMR gene classification rules (Thompson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome sequencing (RNA-seq) is emerging as another tool in the genetic diagnostic toolbox, leading to a reported 7.5-36% improvement in the diagnostic rate depending on the sampled tissue and clinical phenotype (4)(5)(6)(7)(8), and aiding in the prioritization and resolution of variants of uncertain significance (9,10). The approach to RNA-seq analysis varies but generally focuses on differences in splicing and the expression levels of genes.…”
Section: Introductionmentioning
confidence: 99%
“…The approach to RNA-seq analysis varies but generally focuses on differences in splicing and the expression levels of genes. A traditional analytic approach relies on the time-consuming identification of candidate variants first in the ES/GS data that are then manually reviewed in the transcriptome to determine any functional consequences (8)(9)(10). While effective, there are several limitations to this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, RNA genetic test results facilitated classification of 88% of the cancer gene splicing variants selected for analysis as either pathogenic or benign, and was predicted to impact 1 in 43 individuals if performed simultaneously with DNA testing. 9 Thus, a substantial proportion of patients currently receiving DNA testing are likely to benefit from the addition of RNA genetic testing. Several studies have also identified pathogenic deep-intronic variants across a range of hereditary cancer conditions, including hereditary breast and ovarian cancer (HBOC), 10,11 Lynch syndrome, 12,13 familial adenomatous polyposis, 14 neurofibromatosis, 15 and Li-Fraumeni syndrome.…”
Section: Introductionmentioning
confidence: 99%